Social Work and Old Age Policy: An Exploration of Ways to Promote Mental Health in Old Age - Tan, Yiran (International Journal of Social Sciences and Public Administration, 2024)
Under the trend of aging population of the world, the old people’s mental health issues have become the common focus on academic and the social public’s new focus.The core intention of this paper is to examine how social work practices and pension policy measures complement each other to enhance the spiritual well-being of the elderly population, and to deeply analyze the effectiveness of their synergy and the room for strategy improvement. The article begins with an overview of the international and domestic research on the mental health of the elderly, while consolidating the relevant theoretical foundation, covering the nature of mental health, social support theory and life satisfaction theory.Then this article through the detailed analysis of the national and prefecture-level administrative units of the pension policy, insight into the possibility of such strategies in the current policy background and difficulties.Then discusses the social work in the maintenance of elderly mental health aspects of the unique features, such as case coordination, counseling services, community involvement and social network.Through the analysis of specific examples, this study gives consideration to both theory and practice, which not only clarifies the exemplary practical insights, but also extracts practical operational wisdom. Finally, based on the survey feedback, the paper proposes solutions such as strengthening multi-department collaboration, improving the current regulatory framework, and expanding the coverage of limited services.These forward-looking strategy outline research development blueprint, to improve the elderly population in our country the research quality and utility of mental health care services, a lasting and significant impact.